2009
DOI: 10.1002/anie.200901185
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Electroreduction Catalyzed by Gold Nanoclusters: Strong Core Size Effects

Abstract: Bigger isn't better: Gold nanoclusters exhibit enhanced electrocatalytic activity in oxygen reduction when the core size decreased from Au(140) to Au(11), as reflected by the onset potential E(onset) and peak current density J(K) (see picture). The increasing fraction of surface atoms with low coordination numbers and the shift of the d-band center to the Fermi level facilitate oxygen adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
419
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(444 citation statements)
references
References 33 publications
25
419
0
Order By: Relevance
“…The SA values were slightly lower for smaller Au spheres, as compared to those of larger Au spheres and bulk Au (Table 2). This might be due to the effect of particle size on the kinetics of the ORR, which has previously been reported also in alkaline media, [55] however, the difference is too small for that conclusion to be reached. The Au octahedra had a somewhat low SA value, and similarly to the results obtained in acidic solution, the highest SA was determined for Au nanocubes.…”
Section: O 2 Reduction On Au/c Catalysts In 01 M Kohmentioning
confidence: 67%
See 1 more Smart Citation
“…The SA values were slightly lower for smaller Au spheres, as compared to those of larger Au spheres and bulk Au (Table 2). This might be due to the effect of particle size on the kinetics of the ORR, which has previously been reported also in alkaline media, [55] however, the difference is too small for that conclusion to be reached. The Au octahedra had a somewhat low SA value, and similarly to the results obtained in acidic solution, the highest SA was determined for Au nanocubes.…”
Section: O 2 Reduction On Au/c Catalysts In 01 M Kohmentioning
confidence: 67%
“…Similarly, Chen and Chen have shown that smaller AuNPs have higher electrocatalytic activity in alkaline solution. [55] Bron studied the reduction of O 2 in an electrolyte containing sulphuric acid and found that the SA of Au is almost independent of particle size in the range 2.7-42.3 nm. [48] In contrast, Inasaki and Kobayashi have shown that the SA increases with increasing particle size and the number of electrons transferred per O 2 molecule also increases.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] The specifi c characteristics of AuNCs are attributed to the ultra-small size of the NCs ( ∼ 1 nm), where the free electrons are confi ned relative to the Fermi wavelength ( ∼ 1 nm) in the cluster conduction band. Several synthetic methods of AuNCs in solutions have been developed; 1) chemical reduction of Au 3 + ions in the presence of stabilizing agents such as thiol-compounds; [2][3][4][5][6][7] 2) template-assisted synthesis inside the cavities of dendrimers [ 8 ] and proteins; [ 9 ] and 3) core etching of metallic nanoparticles or other NCs into smaller NCs by etching molecules. [10][11][12][13][14] Recently, there has been increasing interest in the development of biological synthesis of AuNCs because of the demand for an environmentally acceptable solvent system and eco-friendly reducing and capping agents ("green chemistry").…”
Section: Introductionmentioning
confidence: 99%
“…[21,48] The slope of the Koutecky-Levich plots is 1/B, which is directly related to the n number of electrons transferred in the ORR process [Eq. (2)].…”
mentioning
confidence: 99%